COMMUNITY SERVICE OF DR. KOFFIE BANDAR LAMPUNG ON DIGITAL MARKETING TRANSFORMATION - Rahman , Fathur; Khamidah, Yuyun; Wulansari , Dita; W.P, M. Firas; Istyqomah, Ajeng; Fitria, Suci; Roslina, Roslina (Devotion: Journal Corner of Community Service, 2023)
Small and medium-sized enterprises (SMEs) is a businesses whose personnel and revenue numbers fall below certain limits. The abbreviation "SME" is used by international organizations such as the World Bank, the European Union, the United Nations, and the World Trade Organization (WTO). SMES contribute to the economy and development of a region. This activity focuses on the digital transformation implemented by Dr. Koffie as one of the SMEs in Bandar Lampung. The activity uses a participatory approach by discussing and presenting material about the importance of digital marketing for businesses. Dr. Koffie uses digital transformation to increase product sales and customers. However, Dr. Koffie can pay more attention to digital developments and optimize online marketing on sites such as Instagram, Facebook, TikTok, and their own website. Dr. Koffie is a coffee shop located in the city of Lampung, that carries a unique concept, namely the beach, with bean bag chairs so that visitors seem to be on the beach.